Cannabis use in people with Parkinson's disease and Multiple Sclerosis: A web-based investigation. (August 2017) - Kindred, John H.; Li, Kaigang; Ketelhut, Nathaniel B.; Proessl, Felix; Fling, Brett W.; Honce, Justin M.; Shaffer, William R.; Rudroff, Thorsten
Highlights: Over 40% of people Parkinson's disease and Multiple Sclerosis are currently using cannabis. Cannabis users reported lower levels of neurological dysfunction. Cannabis may have beneficial effects on mood, memory, and fatigue. Cannabis may negatively affect balance in people with MS. Cannabis users report reducing the amount of prescription medications since starting to use cannabis. Abstract: Objectives: Cannabis has been used for medicinal purpose for thousands of years; however the positive and negative effects of cannabis use in Parkinson's disease (PD) and Multiple Sclerosis (MS) are mostly unknown. Our aim was to assess cannabis use in PD and MS and compare results of self-reported assessments of neurological disability between current cannabis users and non-users. Methods: An anonymous web-based survey was hosted on the Michael J. Fox Foundation and the National Multiple Sclerosis Society webpages from 15 February to 15 October 2016. The survey collected demographic and cannabis use information, and used standardized questionnaires to assess neurological function, fatigue, balance, and physical activity participation. Analysis of variance and chi-square tests were used for the analysis. Results: The survey was viewed 801 times, and 595 participants were in the final data set. Seventy-six percent and 24% of the respondents reported PD and MS respectively. Current users reported high efficacy of cannabis, 6.4 (SD 1.8) on a scale from 0 to 7 and 59% reported reducing prescription medication since beginning cannabis use. Current cannabis users were younger and less likely to be classified as obese ( P < 0.035). Cannabis users reported lower levels of disability, specifically in domains of mood, memory, and fatigue ( P < 0.040). Conclusions: Cannabis may have positive impacts on mood, memory, fatigue, and obesity status in people with PD and MS. Further studies using clinically and longitudinally assessed measurements of these domains are needed to establish if these associations are causal and determine the long-term benefits and consequences of cannabis use in people with PD and MS.